PENGARUH MEA 2015 TERHADAP INTEGRASI PADA SISTEM PERDAGANGAN DI INDONESIA - Mutiara Pratiwi; Murni Daulay (Departemen Ekonomi Pembangunan USU, 2015)
Formulation of the problem in this study is how to predict the impact of Economic Asean Community 2015 to export and import in economic integration trading system in Indonesia. Purpose of this study is to predict export and import changes influenced by Economic Asean Community 2015 in trading system in Indonesia. Hypothesis of this study is to predict the impact Economic Asean Community 2015 to export and import give positive in economic integration trading system in Indonesia. Method of analysis in this study is multiple logarithmic regression. The result of this study is state that export development give positive influence by Economic Asean Community 2015 in economic integration of trading system in Indonesia, but import is not influence by Economic Asean Community 2015 the economic integration of trading system in Indonesia, that is inconsistent with the hypothesis which states that prediction of import development give positive influence by Economic Asean Community 2015 to economic integration of trading system in Indonesia. This is caused by 5,20% decreation of non oil and gas import value and 6,35% increation of oil and gas import value, including raw oil 25,27%, gas 1,02% and decreation of oil 0,39% from 2012 to 2013.Keywords: Impact of Economic Asean Community 2015, export, import